Results of a pilot study using self‐collected mid‐turbinate nasal swabs for detection of influenza virus infection among pregnant women. Issue 3 (May 2015) - Thompson, Mark G.; Ferber, Jeannette R.; Odouli, Roxana; David, Donna; Shifflett, Pat; Meece, Jennifer K.; Naleway, Allison L.; Bozeman, Sam; Spencer, Sarah M.; Fry, Alicia M.; Li, De‐Kun
Abstract : Background: We evaluated the feasibility of asking pregnant women to self‐collect and ship respiratory specimens. Methods: In a preliminary laboratory study, we compared the RT‐PCR cycle threshold (CT) values of influenza A and B viruses incubated at 4 storage temperatures (from 4 to 35°C) for 6 time periods (8, 24, 48, 72, and 168 hours and 30 days), resulting in 24 conditions that were compared to an aliquot tested after standard freezing (−20°C) (baseline condition). In a subsequent pilot study, during January–February, 2014, we delivered respiratory specimen collection kits to 53 pregnant women with a medically attended acute respiratory illness using three delivery methods. Results: CT values were stable after storage at temperatures <27°C for up to 72 hours for influenza A viruses and 48 hours for influenza B viruses. Of 53 women who received kits during the pilot, 89% collected and shipped nasal swabs as requested. However, 30% (14/47) of the women took over 2 days to collect and ship their specimen. The human control gene, ribonuclease P (RNase P), was detected in 100% of nasal swab specimens. However, the mean CT values for RNase P (26·5, 95% confidence interval [CI] = 26·0–27·1) and for the 8 influenza A virus positives in our pilot (32·2, 95% CI = 28·9–35·5) were significantly higher than the CTs observed in our 2010–2012 study using staff‐collected nasal pharyngeal swabs ( P ‐values < 0·01). Discussion: Self‐collection of respiratory specimens is a promising research method, but further research is needed to quantify the sensitivity and specificity of the approach.